Perancangan Departemen Business Development di PT X - Kelvin ayadi Figo; Felecia Felecia (Jurnal Titra, 2021)
PT X is a company which produced galvalume. The company located in Driyorejo, Gresik produces various types of galvalume, including galvalume gutters, galvalume truss, roofing galvalume and hollow galvalume. The company recently created a Business Development department to support the business movement of the company. This new department does not have a business process, job specification and key performance indicators to achieve the goals of this department. In addition, the business development department also does not have a clear job description because it has not been validated by the company. The system redesign of the business development department is needed so that this department can achieve its goals optimally. The existence of business process, job specifications, key performance indicators and clear job descriptions will help workers in the business development department to work better. The result of the business process created is to minimize miscommunication and debate among workers in the business development department. The KPI that has been designed cannot be measured for its implementation because the data is not yet available in the ERP.